2013
DOI: 10.1503/cjs.012912
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the major intraoperative and postoperative complications between unilateral and sequential bilateral total knee arthroplasty in a high-volume community hospital

Abstract: Comparison of the major intraoperative and postoperative complications between unilateral and sequential bilateral total knee arthroplasty in a high-volume community hospital Background: Total knee arthroplasty (TKA) is a common surgical treatment for arthritis. In the event of bilateral knee symptoms, a patient may elect for bilateral TKA (BTKA) under 1 anesthetic or 2 separate unilateral TKAs (UTKA). Controversy exists in the literature regarding the safety of BTKA versus UTKA. We compared the rate of major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Several previous studies have demonstrated a comparable safety profile between bilateral TKR and unilateral TKR in properly selected patients. [12][13][14][15] Patients with bilateral osteoarthritis of the knee should be encouraged to undergo bilateral TKR provided they can tolerate the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have demonstrated a comparable safety profile between bilateral TKR and unilateral TKR in properly selected patients. [12][13][14][15] Patients with bilateral osteoarthritis of the knee should be encouraged to undergo bilateral TKR provided they can tolerate the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The high incidence of cardiovascular complications after simultaneous bilateral TKA has been demonstrated in various studies 18 , 20 , 21) . However, in a recent study by Spicer et al 22) involving 373 bilateral TKAs and 966 unilateral TKAs, bilateral TKA was not associated with increased cardiovascular complications. Still, bilateral TKA has been frequently associated with cardiovascular complications in high risk groups consisting of patients aged 75 years or over.…”
Section: Discussionmentioning
confidence: 82%
“…Instead, candid ates with bilateral knee symptoms who were deemed eligible for surgery were given the option of BTKA or 2 UTKAs. 1 In our experience with patients who present with bilateral fixed flexion knee deformities, even if a UKTA is initially successful, it may develop stiffness and adopt the fixed flexion of the contralateral knee if the latter is not likewise replaced within a few months. Residual flexion contractures after knee replacement have been associated with poor outcomes.…”
Section: The Authors Respondmentioning
confidence: 98%
“…We read Brown and colleagues' re c ent article 1 on culture transition in surgery with interest. We agree with the accompanying editorial by Harvey, 2 that this is an important addition to the literature and that open, frank discussion is needed from the pro fession.…”
Section: Is the Culture Of Surgery Still A Gender Issue?mentioning
confidence: 99%
See 1 more Smart Citation